2022
DOI: 10.22434/ifamr2021.0048
|View full text |Cite
|
Sign up to set email alerts
|

The interaction relationships among agricultural certification labels or brands: evidence from Chinese consumer preference for fresh produce

Abstract: China uses a multilevel agricultural certification system; however, its implications are not well understood. In this study, we used tomatoes as an example in a series of Becker-DeGroot-Marschak auction experiments to determine consumers’ willingness to pay (WTP) toward three safety certification labels and two kinds of brands. Then, based on the auction experiment results, we designed a menu-based choice experiment to assess the interaction relationships between the safety certification labels and brands. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…First, the study did not take into account other attributes of Fuji apples, such as color, freshness, taste, brand, and labeling. However, studies have shown that these attributes also influence consumers’ preference and WTP for fresh products (e.g., Wang and Huo, 2016 ; He et al, 2020 , 2021 ; DeLong et al, 2021 ; Tanemura and Hamadate, 2022 ; Wang et al, 2022 ). Second, our sample was limited to consumers only in six cities in China, so a future study may cover a wider range of urban consumers nationwide to conduct more robust tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the study did not take into account other attributes of Fuji apples, such as color, freshness, taste, brand, and labeling. However, studies have shown that these attributes also influence consumers’ preference and WTP for fresh products (e.g., Wang and Huo, 2016 ; He et al, 2020 , 2021 ; DeLong et al, 2021 ; Tanemura and Hamadate, 2022 ; Wang et al, 2022 ). Second, our sample was limited to consumers only in six cities in China, so a future study may cover a wider range of urban consumers nationwide to conduct more robust tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently, there is no widely accepted way to test and control the impact and presence of experience and learning on WTP. This is particularly important for non-market valuation methods, such as conditional valuation and the Discrete Choice Experiment (DCE) ( Caputo et al, 2020 ; Fang et al, 2021 ; Wang et al, 2022 ), because the products being valued may not be familiar to many respondents ( Bateman et al, 2004 ; Carson and Louviere, 2011 ; Czajkowski et al, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For these companies, in fact, in addition to renouncing the use of synthetic products, paying attention to reducing water use and CO 2 emissions from transportation, recycling materials, or any of the other 10 indicators in the specification are equally important. This means that there are entrepreneurs who care not only about profit but also about the environment [57,58]. These M-L companies are integrated and propulsive parts of the area in which they are located, so the way they operate is conscious of and in tune with all territorial components (i.e., social, environmental, economic).…”
Section: Multidimensional Scaling-winemakersmentioning
confidence: 99%
“…Indeed, certainly producers of small and micro wine enterprises are aware of the importance of applying agro-ecological practices. However, the risk of not being competitive due to the high costs to be incurred for the greening transition is very high [58]. For this reason, SOStain indicators are approached differently from larger vs. smaller enterprises.…”
Section: Multidimensional Scaling-winemakersmentioning
confidence: 99%
See 1 more Smart Citation